Pengaruh Persepsi Nilai Pelanggan terhadap Adopsi menggunakan Bank Syariah - Fadila, Dewi (Jurnal Ilmu Manajemen, 2023)
Islamic banking in Indonesia is the largest retail banking in the world. Indonesian sharia banking has been recognized worldwide as an unquestionable and applicable sharia bank so that it becomes an example of reference and a place of learning for sharia banks from various countries. The problem currently faced by Islamic banking in Indonesia is how to make the majority Muslim community become customers in Islamic banking. Islamic banks in Indonesia face a major problem in getting Muslims to become customers. This study aims to determine whether the supporting functional values, professionalism functional values, fairness values, emotional values and social values influence the adoption of Islamic banking. As well as whether the dominant variable influences the adoption of using Islamic banks. The population in this study were Islamic bank savings customers in Palembang City, which consisted of Bank Sumsel Babel Syariah, Bank Syariah Indonesia, Bank Muamalat, OCBC Syariah with a sample of 370 people. The results of the study found that supporting functional values, professionalism functional values, fairness values, emotional values and social values jointly affect the adoption of using Islamic banking with social values as the most dominant values in this study.